2002
DOI: 10.1046/j.1432-1033.2002.03061.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of amino‐acid residues Q39 and E451 in the determination of substrate specificity of the Spodoptera frugiperdaβ‐glycosidase

Abstract: The design of b-glycosidases with planed substrate specificity for biotechnological application has received little attention. This is mostly a consequence of the lack of data on the molecular basis of the b-glycosidase specificity, namely data on the energy of the noncovalent interactions in the enzymetransition state complex. In an attempt to fill this gap, sitedirected mutagenesis and enzyme steady-state kinetic experiments with different substrates were conducted, using as model a digestive b-glycosidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 24 publications
4
38
0
8
Order By: Relevance
“…The combination of these data with the growing number of b-glycosidases sequences classified in the GH family 1 (1) has allowed the identification of several amino acid residues potentially involved in the substrate specificity in hundreds of b-glycosidases. Characterization of the non-covalent interactions between b-glycosidase active site and substrate (20,21) revealed that subsite 71 specificity is determined by a hydrogen bond network between glycone hydroxyls and active site residues. However, the importance of the majority of the active site residues of b-glycosidases still remains to be determined, especially those involved in the aglycone specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of these data with the growing number of b-glycosidases sequences classified in the GH family 1 (1) has allowed the identification of several amino acid residues potentially involved in the substrate specificity in hundreds of b-glycosidases. Characterization of the non-covalent interactions between b-glycosidase active site and substrate (20,21) revealed that subsite 71 specificity is determined by a hydrogen bond network between glycone hydroxyls and active site residues. However, the importance of the majority of the active site residues of b-glycosidases still remains to be determined, especially those involved in the aglycone specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of microbial b-glucosidase genes have been expressed in either E. coli, yeast or fungi (Pandey and Mishra, 1997;Saloheimo et al, 2002;Li et al, 2004;Hong et al, 2007) studies on heterologous expressions of insect b-glucosidases are still limited (Marana et al, 2002;Byeon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The substrate subsite of ␤-glycosidases in GH family 1 contains six highly conserved amino acid residues (Gln-24, His-125, Asn-169, Trp-404, Glu-411, and Trp-412 in Abg). These conserved residues in the glycone pocket play important roles in recognizing substrates (49,50). Met-407 in AbgE358G is located in the loop between the 8th strand and the 8th helix and Glu-411, Trp-412, and Trp-404, which are components of the glycone (Ϫ1) subsite and interact with the equatorial C3-and C4-hydroxyl groups of glucose, are placed at the ends of this loop (Fig.…”
Section: Discussionmentioning
confidence: 99%